Rosenshine's principles in action. - Sherrington, Tom., ....-; Caviglioli, Oliver, ....- (Melton, Woodbridge : John Catt Educational Ltd, 2019)
Barak Rosenshine's Principles of Instruction are widely recognized for their clarity and simplicity and their potential to support teachers seeking to engage with cognitive science and the wider world of pedagogic theory. In this concise new guide, Rosenshine fan Tom Sherrington amplifies and augments the principles and further demonstrates how they can be put into Practice in everyday classroom. The second half of the book contains Rosenshine's original paper "Principles of Instruction", as published in 2010 by the International Academy of Education (IAE) - a paper with a superb worldwide reputation for relating research findings tot classroom practice. Together with Sherrington's brilliant and practical commentary, it forms a powerful handbook for teachers at all levels.
Keywords: Didactiek, klasdidactiek